Efficacy of platelet rich plasma in chronic leg ulcers: a prospective randomized controlled study - Wanniang, Naphisabet; Shukla, Pankaj; Pai, Varadraj V. (International Journal of Research in Dermatology, 2020)
Background: Chronic wounds affect approximately 1-2% of the population in Europe and the United States. Platelet rich plasma (PRP) has emerged as an effective, inexpensive, minimally invasive treatment modality for chronic leg ulcers. Objective of the study was to evaluate the efficacy of PRP, and to compare the effectiveness of PRP to regular antiseptic dressing in the management of chronic leg ulcers. Methods: A hundred patients with chronic leg ulcers of more than 6 weeks duration were randomized into two groups (PRP and conventional dressing group). Patients in the PRP group received weekly intradermal injections of PRP to the wound in addition to conventional daily dressings till complete healing of the ulcers or up to a maximum of 6 weekly PRP sessions. Percentage of improvement in the area and volume of the ulcers were recorded. Patients were followed up at 1 month post PRP treatment. Results: The mean reduction in the area of the ulcers at the end of 6 weeks was 66.39% in the PRP group and 28.6% in the control group. The mean reduction in volume of the ulcers at the end of 6 weeks was 71.80% and 37.88% in the case and control group respectively. At the end of 1 month post treatment follow-up, 74% and 10% of the ulcers treated with PRP and with conventional dressing respectively showed complete healing. Conclusions: Leg ulcers treated with PRP showed a significantly higher reduction in the area and volume of the ulcers compared to ulcers treated with conventional moist dressing.